Reduced order generalised integrator-based current controller applied to shunt active power filters - Gómez Jorge, Sebastián (2014)
This study proposes the application of a current controller based on the reduced order generalised integrator (ROGI) to control a three-phase three-wire shunt active power filter (SAPF). The ROGI-based controller has low computational burden and it is suitable for its implementation in low-cost digital signal processors (DSPs). This controller is also frequency adaptive. This allows it to maintain its high steady-state performance despite grid frequency variations. Unlike conventional high performance SAPFs this current controller does not require the computation of high quality current references (with low distortion and total harmonic distortion below that recommended by the IEEE Std 519-1992). Therefore most of the available computational power can be used for compensating the harmonics produced by the load.